Burial in the Homeland as the Highest Dreams of the Exiles: Postcolonialism in the Modern Arabic Novel - Mahmudah; Amina Tahraoui (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2024)
This research aims to show the strategy adopted by Arab exiles in modern Arabic novels to return to their homeland by making a testament for repatriating their bodies after they die. Considering that the phenomenon of the outcasts is an effect of Western colonialism in the Arab world, this research uses a postcolonial perspective to approach the topic. Using an interpretive method, the exiles' desire to be buried in the homeland will be examined in three novels: Lailatu al-Milyār (1986), Sahrah Tanakkuriyyah lil-Mautā (2003) by Gādah as-Sammān (Syrian Lebanese), and Maṣā`ir: Kūnsyirtū al-Hūlūkūst wa an-Nakbah (2015) by Raba’ī al-Madhūn (Palestinian). The results of the analysis show that: (1) exiles made testament to their offspring to be buried in the homeland to ensure the connection, (2) socio-economic conditions in exile and socio-politics in the homeland make the testament failed to be realized, (3) the effects of inability to fulfill the testament had become a way for the offspring to get to know and love the homeland despite of the distance. Even though returning to the homeland is proved impossible, this strategy of exiles had succeeded in raising nationalism in their offspring. The futility of returning to Palestine seems greater than to Lebanon, considering that Israel has occupied Palestine.